Private Schadensgestaltung als Drittbelastung : Fangpr̃mien, Vertrags- und Verbandsstrafen: Regressf̃hige Schadensposten oder unzul̃ssige Rechtsgesch̃fte zu Lasten Dritter? - Odijk, Paul van (Schriften zum bürgerlichen Recht ;, 2022)
The thesis examines the question of the extent to which premiums, contractual and association penalties constitute compensable damages or inadmissible legal transactions to the detriment of third parties. Based on the proposal developed for dealing with third party burdens, the private damage arrangements present themselves as disproportionate legal transactions to the detriment of third parties. As a result, they are relatively ineffective and therefore do not represent a compensable damage.